Global Trends in teacher education - Selvam, S.K. Panneer (New Delhi : A.P.H Publishing, 2009)
A teacher has to deal with a child. A child is an infinitely subtle and sensitive person. A teacher, therefore, must be loving and lovable in all his efforts. He must have the qualities of an artist, an entrepreneur and a mother part-time. Unless he has physical psychological and sociological capacities he could not perfect the Instruments of knowledge. There are rnany world renowned institutions because of teachers. Recent societal and powerful economic changes view teacher and teaching from a market of oriented economy. So learning community, with a consumer attitude put new pressures on and place new demands from teaching institutions. Quite naturally more parents want to assure a decent living for their children. In future knowledge society only will survive. Knowledge should be viewed as a fully integrated social activity instead of dumping of brain with more informations. Hence, out, going students of colleges or universities should have skills, capable of critical thinking, building more vibrant and civil communities. Are these points broadly discussed in this edition, taking into consideration the global trends in teaching, various programmes and projects are proposed and recommended. Teaching community will be enriched by this book.
Keywords: Teachers -- Training of; Education and globalization